2022
DOI: 10.3847/1538-4357/ac8050
|View full text |Cite
|
Sign up to set email alerts
|

CO Excitation and its Connection to Star Formation at 200 pc in NGC 1365

Abstract: We report high-resolution (2″ ∼ 200 pc) mappings of the central region of the nearby barred spiral galaxy NGC 1365 in the CO(1–0) and CO(2–1) emission lines. The 2–1/1–0 ratio of integrated intensities shows a large scatter (0.15) with a median value of 0.67. We also calculate the ratio of velocity dispersions and peak temperatures and find that in most cases the velocity dispersion ratio is close to unity and thus the peak temperature ratio is comparable to the integrated intensity ratio. This result indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The increase of the line width in the inflow regions of NGC 3351 (r  500 pc) is also notable, reaching comparable values to its central nucleus and being higher than in the other two galaxies. Contrary to most situations where T peak dominates the integrated intensity variation (e.g., Egusa et al 2022), T peak is consistently low in the NGC 3351 inflows, and thus the enhanced velocity dispersion plays a more important role in the observed CO emission of this region.…”
Section: Spectral Line Widths and Peak Temperaturesmentioning
confidence: 54%
“…The increase of the line width in the inflow regions of NGC 3351 (r  500 pc) is also notable, reaching comparable values to its central nucleus and being higher than in the other two galaxies. Contrary to most situations where T peak dominates the integrated intensity variation (e.g., Egusa et al 2022), T peak is consistently low in the NGC 3351 inflows, and thus the enhanced velocity dispersion plays a more important role in the observed CO emission of this region.…”
Section: Spectral Line Widths and Peak Temperaturesmentioning
confidence: 54%
“…Further out (beyond the inner R gal 12″) in the northern and southern bar lanes that run along the large-scale bar (Leroy et al 2021a;Egusa et al 2022), overlapping gas streamlines lead to more complex gas kinematics, often with multiple peaks observed along the same line of sight. Ongoing massive star formation, meanwhile, is distributed in an asymmetric fashion along the bar lanes, with many cluster candidates associated along the full length of the northern lane, while the southern lane lacks clusters at larger radii despite fairly high integrated CO intensities.…”
Section: Gas Flows and Turbulent Motions In The Barmentioning
confidence: 99%
“…35 The nucleus harbors a number of compact radio sources and a large number of super star clusters, with star formation taking place mostly in an elongated circumnuclear ring (e.g., Kristen et al 1997;Forbes & Norris 1998;Stevens et al 1999;Galliano et al 2005;Alonso-Herrero et al 2012;Fazeli et al 2019), which likely corresponds to the inner Lindblad resonance at r ≈ 1 kpc reported by Lindblad et al (1996). This ring is very rich in molecular gas (Sandqvist et al 1995;Sakamoto et al 2007;Gao et al 2021;Egusa et al 2022). The AGN is known to drive a biconical outflow seen in ionized gas (e.g., Storchi-Bergmann & Bonatto 1991;Veilleux et al 2003;Venturi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For NGC 1365, the CO(1-0) data were observed using the 12 m array and ACA under two projects, namely 2015.1.01135.S and 2017.1.00129.S. Using these data sets, Egusa et al (2022) made a CO(1-0) cube with a beam size of 2 0 and a median rms of 0.23 K. In this study, we use this cube, after convolving it to a beam size of 15″. Other galaxies were observed only by ACA, under the projects 2019.2.00052.…”
Section: Sfr Surface Densitymentioning
confidence: 99%